Anticipation Can Be More Common in Hereditary Spastic Paraplegia with SPAST Mutations Than It Appears. (6th September 2022) - Hashemi, Seyyed-Saleh; Hajati, Reza; Davarzani, Atefeh; Rohani, Mohammad; DanaeeFard, Fardad; Rahimi Bidgoli, Mohammad Masoud; Fatehi, Farzad; Kariminejad, Ariana; Najmabadi, Hossein; Nafissi, Shahriar; Alavi, Afagh
ABSTRACT: Background and objective: Hereditary spastic paraplegia (HSP) is a heterogeneous neurodegenerative disorder with lower-limb spasticity and weakness. Different patterns of inheritance have been identified in HSP. Most autosomal-dominant HSPs (AD-HSPs) are associated with mutations of the SPAST gene (SPG4), leading to a pure form of HSP with variable age-at-onset (AAO). Anticipation, an earlier onset of disease, as well as aggravation of symptoms in successive generations, may be correlated to SPG4. Herein, we suggested that anticipation might be a relatively common finding in SPG4 families. Methods: Whole-exome sequencing was done on DNA of 14 unrelated Iranian AD-HSP probands. Data were analyzed, and candidate variants were PCR-amplified and sequenced by the Sanger method, subsequently checked in family members to co-segregation analysis. Multiplex ligation-dependent probe amplification (MLPA) was done for seven probands. Clinical features of the probands were recorded, and the probable anticipation was checked in these families. Other previous reported SPG4 families were investigated to anticipation. Results: Our findings showed that SPG4 was the common subtype of HSP; three families carried variants in the KIF5A, ATL1, and MFN2 genes, while five families harbored mutations in the SPAST gene. Clinical features of only SPG4 families indicated decreasing AAO in affected individuals of the successive generations, and this difference was significant ( p -value <0.05). Conclusion: It seems SPAST will be the first candidate gene in families that manifests a pure form of AD-HSP and anticipation. Therefore, it may be a powerful situation of genotype–phenotype correlation. However, the underlying mechanism of anticipation in these families is not clear yet.